Learning in the age of AI: The case of international graduate students in U.S. higher education - Bayeck, Rebecca Y; Ameko, Stephen K. (Journal of International Students, 2026)
International graduate students face unique linguistic, cultural, and academic challenges in U.S. higher education, and the increasing influence of artificial intelligence (AI) adds new opportunities and adjustments to their learning practices.  In this study, we examine how international graduate students interact with AI to navigate learning in their new environment. Findings show that students use AI in various ways as they navigate their new learning environment. These include using AI to summarize readings; proofread writings; help with their writing; adjust to the new learning environment; and collaborate with AI as a friend and learning companion. Though participants recognize that AI can be misleading, they still encourage its critical use. These findings reveal students engage in AI-mediated learning.